The Progression from Repositories to Institutional Repositories: a Comparative Examination of Repositories at the Durban University of Technology and Stellenbosch University - Raju, Roy; Raju, Reggie (My University, 2010)
The South African higher education environment was re-landscaped to redress, inter alia, an apartheid higher educational system. In this re-landscaping process, the M.L.Sultan and Natal Technikons were merged to create the Durban University of Technology (DUT). This newly formed University of Technology had to transform from a vocationally focused institution to an institution striving for exponential growth in research and postgraduate student output. Stellenbosch University (SU), on the other hand, is a traditional university with a history of excellence and a claim to be a leading research institution in Africa. Given the history of these institutions, the road to be travelled for the adoption of an institutional repository (IR), is interpreted to be the same, but different in terms of challenges: as described by Thomas et al. (2005: 65), “the same destination with different paths”. Hence the purpose of this paper is to examine these different paths. However, before engaging in the discussion about the paths traversed by each of these institutions, it is important to tease out the fundamental principle governing IRs and the influence of these in formulating policy and procedures.
Keywords: ICADLA, conference, digital library, archive, Stellenbosch, DUT, Durban